FACTORS INFLUENCING OCCUPATIONAL STRESS AMONG NURSES IN GULU REGIONAL REFERRAL HOSPITAL, GULU CITY A CROSS-SECTIONAL STUDY. - Prisca Alanyo; Donatus Kimera (Student's Journal of Health Research, 2023)
Background:  The purpose of the study was to assess the factors influencing occupational stress among nurses at Gulu Regional Referral Hospital, Gulu City. Methodology: This descriptive cross-sectional study took a quantitative research approach and it was conducted in Gulu Regional Referral Hospital, Gulu City. A sample of 30 nurses was selected using the convenience sampling method. A structured questionnaire was used to collect data and it involved both open and closed-ended questions. The data collected was presented in the form of tables, pie charts, and graphs for analysis. Results: Study results revealed that; 14(47%) were aged between 26-30 years, 23(77%) were female, and 30(100%) experienced stress while at work, with 12(40%) faced with a lot of demands from work and family. Results also revealed that 20 (67%) received supervision and training during their work to enable them to get relieved of stress, while 17 (56%) never received rewards at the facility when they worked hard. 28 (93%) faced some stressful moments with patients during work, 24 (80%) found caring for the dying so stressful and successful, 30 (100%) found that caring for uncooperative patients caused work-related stress, and 17 (57%) agreed that caring for severely ill patients is not interesting and it is frustrating. Conclusion:  This research established that, although the nurses liked their job and perceived their profession as interesting, they experienced stress while caring for the severely ill, uncooperative patients and the dying. Recommendation: The government of Uganda should improve the working conditions of the nurses to reduce the stress at the workplace by recruiting more staff, conducting CMEs on stress management and improving their salaries.